The importance of inflammation markers in polycystic ovary syndrome - Özay,Ali Cenk (2021)
SUMMARY OBJECTIVE: This study aimed to examine inflammation markers in patients with polycystic ovary syndrome (PCOS) and to compare them with healthy women. METHODS: This prospective study was conducted by examining patients who applied to the Near East University Gynecology and Obstetrics Outpatient Clinic between January 2019 and January 2020. A total of 110 PCOS patients with 135 control groups were compared in terms of metabolism, hormonal factors, and inflammation markers. RESULTS: The neutrophil count, neutrophil–lymphocyte ratio (NLR), platelet, platelet–lymphocyte ratio (PLR), platelecrit (PCT), erythrocyte cell distribution width, platelet distribution width, mean platelet volume, and C-reactive protein (CRP) values were found to be statistically significantly higher in patients with PCOS. There was a positive correlation between inflammation markers and serum androgens. Also, a positive correlation was observed between inflammation markers and cardiovascular risk parameters. In receiver operating characteristic curve analysis, the most valuable parameter in distinguishing PCOS patients from healthy controls was serum CRP levels [areas under the curve (AUC)=0.928, 95%CI 0.894–0.963, p<0.001, 92.6% sensitivity, and 82.7% specificity]. CONCLUSIONS: Serum CRP, neutrophil count, and PCT and NLR levels are valuable markers that show the inflammatory process in PCOS patients.